Exploring the impact of platform leadership on employee innovative behavior: a sequential explanatory mixed method - Yuyi, Mengting; Li, Ying; Zhu, Xin; Shahid Khan, Muhammad (Frontiers in Psychology, 2025)
This study uses the Ability—Motivation—Opportunity framework to explore the influence mechanism of platform leadership on employees’ innovation behavior. This study examines organizational learning, knowledge sharing, coworker support, and psychological empowerment as mediating variables, employee innovation behavior as the dependent variable. This study constructs a multi-mediated model to analyze the impact of platform leadership on employee innovative behavior, which includes 13 hypotheses. The study primarily focuses on data collected from China’s Shanxi and Guangxi regions, encompassing manufacturing, software and information services, internet companies, and enterprises establishing digital platforms, with individual employees as the subjects of investigation. This research employed a mixed-method approach, following a standardized research process in a sequential explained process. Research one involved the analysis of questionnaires from 518 employees, which applies to a structural equation model. The model’s multiple mediation effects are confirmed using the bootstrap method. Research two comprised semi-structured interviews with 24 enterprise employees. Text data mining is conducted using Python and the open-source Chinese tool “Weiciyun” to explore the underlying mechanisms between platform leadership and innovation behavior. This study underscores the practical contributions of platform leadership to organizational development by demonstrating its positive impact on organizational learning, knowledge sharing, coworker support, and psychological empowerment, all of which significantly enhance employee innovation behavior. Organizational learning emerges as the most critical mediator. The findings provide actionable insights for leadership policies, emphasizing the importance of cultivating a learning-oriented culture, fostering knowledge sharing, and empowering employees psychologically. By implementing these strategies, leaders can effectively drive innovation and improve organizational performance, offering a clear pathway for leadership practices to enhance adaptability and innovation within organizations.